A case of refractory immune checkpoint inhibitor‐induced colitis with Clostridioides difficile infection. Issue 1 (17th October 2022) - Okura, Yukito; Kobayashi, Katsumasa; Yamada, Yurina; Furuya, Makoto; Kitano, Naoki; Oshina, Eri; Matsuoka, Mana; Nozaka, Takahito; Tashiro, Yoshihiro; Sato, Ayako; Yauchi, Masato; Matsumoto, Taichi; et al.
Abstract: The clinical symptoms of an immune checkpoint inhibitor (ICI)‐induced colitis are similar to those of ulcerative colitis. ICI‐induced colitis, like ulcerative colitis, may be complicated by other colitis, such as Clostridioides difficile infection (CDI). A 72‐year‐old man was admitted because of watery and bloody stools 10 times a day after three courses of nivolumab (antibodies against programmed death 1) and ipilimumab (cytotoxic T‐lymphocyte‐associated antigen‐4) for stage IV renal cell carcinoma. Colonoscopy revealed erythema and multiple erosions in the colon. Histopathological examination of colonic mucosa revealed diffuse inflammatory cell infiltration and apoptosis. The initial cytomegalovirus antigen test and C. difficile detection assay results were negative. Based on these findings, we diagnosed the patient with ICI‐induced colitis and discontinued ICI therapy. The symptoms did not improve despite the administration of Prednisolone and infliximab. A repeat colonoscopy revealed a new appearance of pseudomembranes from the sigmoid colon to the rectum one month after the start of these treatments. At this point, the patient tested positive for C. difficile . With treatment with vancomycin for CDI, the abdominal symptoms gradually decreased. Nivolumab alone was cautiously restarted. However, no colitis recurrence and further tumor reduction were observed. Here, we report our experience of a case of refractory ICI‐induced colitis complicated by CDI. ICI‐induced colitis may be complicated by CDI and should be carefully treated with repeated CDI testing if refractory to treatment. We believe that our observation will provide helpful information for determining an appropriate treatment strategy for ICI‐induced colitis.